Ichthyofauna of the lower course of the Negro river drainage, Patagonia Argentina - Soricetti, Mariano (2020)
The drainage of the Negro River is the most important watercourse in the Patagonia ecoregion and, together with the Colorado river basin, define an ecotone, i.e., a zoogeographic transition, where coexist the Brazilian and Patagonian lineages of freshwater fishes. The Patagonia ecoregion has 29 fish species, 15 native and the remaining introduced. For this study, the ichthyofauna of seven locations in the lower course of the Negro river drainage were sampled along two years. Gillnets, coastal trawls, cast nets, river trammel nets and fishing rods were used to catch specimens. A total of 13 species belonging to nine orders and 11 families were collected. The families Atherinopsidae and Characidae show the highest species richness and one exotic species, Cyprinus carpio Linnaeus, 1758, was recorded. The origin and distribution of some species is discussed, considering the role of human action and certain environmental factors.